An Analysis of Classroom Interaction in Cooperative Learning New Insights for Secondary School English Teachers - Noora Abdul Kader (Educational Quest, 2013)
Cooperative learning is one of the main instructional strategies that can be used to create a non-threatening environment, which encourages participation and promotes positive social interactions. The study is intended to analyze the perception of secondary school English teachers regarding constrains met by them for the successful implementation of cooperative learning in classroom. Investigator also made an attempt to find out the difficulties met by secondary school students in English classroom in using English as a second language while engaged in cooperative learning. The study followed the method of survey on a sample of 120 secondary school students and 40 secondary school English teachers from the state of Kerala. Findings of the study revealed several factors which may serve as an eye opener for English language teachers for making cooperative learning more close to the students. Practical suggestions for the problems were highlighted by the investigator in the study.